How do Teachers Enhance Elementary School Students’ Numeracy Through the Integration of Singing and Jarimatika Methods? - Novitasari, Welly; Herwin (Jurnal Penelitian Pendidikan, 2023)
This research aims to reveal teachers' efforts to improve the numeracy of lower grade elementary school students using singing and Jarimatika methods. This research is a type of qualitative research with a case study approach. Research data was collected from elementary school teachers and low-grade elementary school students using observation and interviews. The results of the research show that the teacher's efforts to integrate the singing and Jarimatika methods were carried out using the song "Balonku Ada Lima" whose lyrics were replaced with addition and subtraction rules using the Jarimatika method. Jarimatika rules are taught by singing while simulating number symbols to introduce the concept of place value. Improving number operation skills is carried out by combining the concept of scaffolding, peer tutoring, and drill and practice of calculating using Jarimatika. This combination of methods aims to make it easier for students to strengthen their numeracy skills using Jarimatika method.